Family business longevity going against the odds : an analysis of the factors enabling family businesses to thrive beyond the third generation - Pierro, Elisa; Jurek, Martin; Pernica, Karel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Family businesses play a crucial role in the worldwide economy, given their impact on countries’ GDP and employment rate. However, many of them are yearly dismissed and a small percentage of them reaches the third generation. Succession is a sensitive topic and the transition from the second to the third generation can be particularly challenging. The goal of this thesis research is to investigate and explore the potential factors that enable family businesses to thrive across generations, with a focus on Italian family businesses in the food and wine sector. This thesis employs a qualitative approach, using semi-structured interviews with family members working/managing/owning the family business to better understand the key factors in the company’s longevity. The research findings highlight a positive correlation between generational entrepreneurship and business survival, while the lack of formal written documents, such as family constitution, was prevalent in all the companies. While taking into consideration the limitations of the research, it still provides valuable insights to the field of family businesses.
Vedoucí práce: Martin Jurek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses